A longitudinally expanded Ni-based metal–organic framework with enhanced double nickel cation catalysis reaction channels for a non-enzymatic sweat glucose biosensor. Issue 39 (15th September 2020) - Xuan, Xiaoyang; Qian, Min; Pan, Likun; Lu, Ting; Han, Lu; Yu, Huangze; Wan, Lijia; Niu, Yueping; Gong, Shangqing
Abstract : A longitudinally expanded Ni-Based metal–organic framework with enhanced double nickel cation catalysis reaction channels was used for a non-enzymatic sweat glucose biosensor. Abstract : Nickel-based metal–organic frameworks (Ni-MOFs) have attracted increasing attention in non-enzymatic glucose sensing. However, the insufficient active Ni cation sites from a stacked MOF layer, the unclear Ni catalysis mechanism, and the severe liquid alkaline electrolyte remain challenging for practical applications. In this work, the sonication-induced longitudinal-expansion of Ni-MOFs increases the active nickel ion sites, which not only enhances the current response to glucose detection, but also shows the oxidation peak evolution of nickel ions with different sonication times, revealing the mechanism of different glucose detection channels. The Ni-MOF sonicated for 60 min (60 min Ni-MOF) displays enhanced Ni(iii )/Ni(ii ) and more significant Ni(iv )/Ni(iii ) double nickel cation channels for catalyzing glucose into glucolactone compared to the 0 min Ni-MOF (without sonication), showing optimized glucose detection ability with a high sensitivity of 3297.10 μA mM −1 cm −2, a low detection limit of ∼8.97 μM (signal-to-noise = 3) and a wide linear response range from 10 to 400 μM from the cyclic voltammetry test as well as a high sensitivity of 3.03 μA mM −1 cm −2, a low detection limit of ∼1.16 μM (signal-to-noise = 3) and a wide linear response range from 10 to 2000 μM from the chronoamperometry test. More importantly, an all-solid-state glucose biosensor using a PVA/NaOH solid-state electrolyte and a disposable 60 min Ni-MOF working electrode is assembled for non-enzymatic sweat glucose detection.